Peran Kompensasi dalam Meningkatkan Kinerja Karyawan pada Pt. X di Kab. Sorong - Pandiangan, Hendrik; Nurlela, Nurlela (Journal of Economics, Bussiness and Management Issues, 2024)
This study examines the role of compensation in improving employee performance at PT. X, located in Sorong Regency. The objective of this research is to analyze the impact of compensation on employee motivation and performance within the company. The study was conducted at PT. X, involving a total of 15 respondents selected through purposive sampling. The research employed a qualitative method with descriptive and narrative approaches, collecting data through interviews and document analysis. Data analysis techniques included data reduction, data presentation, and coding to uncover factors influencing employee performance.The results indicate that fair compensation, both financial and non-financial, can enhance employee motivation, satisfaction, and performance. Providing compensation that aligns with employee contributions can reduce conflicts and increase productivity. Furthermore, the application of ethical principles in compensation practices plays a crucial role in fostering a healthy, fair, and professional work environment. It is hoped that this study will provide deeper insights into compensation management in companies with similar characteristics.